“Utilización de gallinaza como fuente de fertilización orgánica en el rendimiento de maracuya (passiflora edulis S.), bajo condiciones de suelos ácidos en San Martín” - Grández Bardales, Manuel Oscar (2004)
The present investigation work was carried out, with the object to determine the effects of the security with hen excrement, comparing witness with and without chemical fertilization in the yield of fruit passion during the first year of production and to determine the analysis of profitability of the treatments in study. lt was carried out in the Experimental Station from the lnstitute of Tropical Cultivations to 2.5 Km of Tarapoto, district Band of Shilcayo, county and department of San Martín. Whose geographical location: South latitude 06°30'07", Longitude West 76°20'09", Altitude 360 msnm; in a sandy frank texture soil, with pH 3.8 to 4.0 and climate with temperature average 25.81 ºC and precipitation of 1202.4 7 mm per year. The design DBCA was used with 5 treatments (absolute Witness, hen excrement 2, 4 and 8 TM/ha, and complementary Witness with NPK 100-70-150) and 4 repetitions. The registered Parameters were: plant height to the 15, 30 and 45 dds, days to the flowing, number of flowers and fruits for plant, total number of fruits harvested in one year and total weight of harvested fruits. The best results were obtained paying to the fruit passion with 4 hen excrement tlha, beginning their flowing in 72 days, with 134.1 flowers/plant, 112.15 fruits/plant and a yield average of 4 1875 kg/ha; achieving a gain of S l. 0.45 for each new invested sun. The value of this investigation impacts in the contribution like option to manage impoverished floors, taking advantage of a rich security source in organic matter, of relative low cost and in an abundant way in the area, like it is the hen excrement.